Descriptive epidemiology of changes in weight and weight-related behaviours of Australian children aged 5 years: two population-based cross-sectional studies in 2010 and 2015 - Hardy, Louise L (BMJ Open, 2018)
OBJECTIVE: Over the past 10–15 years there has been substantial investment in New South Wales (NSW), Australia, to reduce child obesity through interventions in children aged 0–5 years. We report changes in weight and weight-related behaviours of 5-year-old children. DESIGN: Cross-sectional surveys conducted in 2010 and 2015. SETTING: NSW schools (2010 n=44; 2015 n=41) PARTICIPANTS: Australian children in kindergarten (2010 n=1141 and 2015 n=1150). OUTCOME MEASURES: Change in anthropometry and indicators of diet, screen time, school travel and awareness of health recommendations. Additionally, we examined 2015 differences in weight-related behaviours by sociodemographic characteristics. RESULTS: Prevalence of overweight/obesity was 2.1% lower (adjusted OR (AOR) 0.83, 95% CI 0.67 to 1.04) and abdominal obesity 1.7% higher (AOR 1.35, 95% CI 0.93 to 1.98) in 2015 than 2010. Significant improvements in multiple weight-related behaviours were observed among children in the highest tertile of junk food consumption (AOR 0.63, 95% CI 0.50 to 0.80), rewarded for good behaviour with sweets (AOR 0.59, 95% CI 0.47 to 0.74) and had a TV in their bedroom (AOR 0.65, 95% CI 0.43 to 0.96). In 2015, children from low socioeconomic neighbourhoods and non-English-speaking backgrounds were generally less likely to engage in healthy weight-related behaviours than children from high socioeconomic status neighbourhoods and from English-speaking backgrounds. Children in these demographic groups were less likely to eat breakfast daily, have high junk food intake and eat fast food regularly. Children from rural areas tended to have healthier weight-related behaviours than children from urban areas. CONCLUSIONS: There were significant positive changes in 5-year-old children’s weight-related behaviours but children from low socioeconomic neighbourhoods and from non-English-speaking backgrounds were more likely to engage in unhealthy weight-related behaviours than children from high socioeconomic neighbourhoods and English-speaking backgrounds. The findings indicate that there is a need to enhance population-level efforts and ensure community programmes are targeted and tailored to meet different subpopulation needs.